2002
DOI: 10.1080/01932690208984189
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Oil-Water Systems Near the Affinity Inversion. XII. Emulsion Drop Size Versus Formulation and Composition

Abstract: Emulsion drop size depends on the both fo rmulation and compos ition of the surfactant-oil-water system. as well as on the stirring conditions prevailing during emulsification. General trends versus f ormulation or compos ition changes are presented. Howevel; it is shown that the effects are not independent and that a prop er combination of these param eters allows the attainm ent of vel)' small drop size. even at low stirring energy. An overall phenomenology is presented on a twodimensional fo rmulation-comp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 35 publications
2
28
0
2
Order By: Relevance
“…On the other hand, Lin (1978) reported that in some emulsions stabilised with non-ionic surfactants, it may be desirable to keep the emulsification temperature above the PIT in order to facilitate emulsification. Salager and co-workers (Perez et al, 2002;Salager et al, 2002) confirmed and enhanced those statements by arguing that the opposite effects of formulation (temperature in our case) on interfacial tension and emulsion stability resulted in the presence of a minimum droplet size close to but not on the line HLD ¼ 0, and on both sides of it (see also Pizzino et al, 2009). They also added that small droplet emulsions can be attained near the vertical lines at high internal phase ratios.…”
Section: Catastrophic Inversionsupporting
confidence: 80%
“…On the other hand, Lin (1978) reported that in some emulsions stabilised with non-ionic surfactants, it may be desirable to keep the emulsification temperature above the PIT in order to facilitate emulsification. Salager and co-workers (Perez et al, 2002;Salager et al, 2002) confirmed and enhanced those statements by arguing that the opposite effects of formulation (temperature in our case) on interfacial tension and emulsion stability resulted in the presence of a minimum droplet size close to but not on the line HLD ¼ 0, and on both sides of it (see also Pizzino et al, 2009). They also added that small droplet emulsions can be attained near the vertical lines at high internal phase ratios.…”
Section: Catastrophic Inversionsupporting
confidence: 80%
“…If salt does indeed allow more packing at the interface, one would expect droplet size to decrease with increased salinity in order to accomodate more possible particles at the interface. Although some studies have shown an increase in dispersed oil droplet size as salinity increased [47,49], the effect seems to be system dependent. We hypothesize that although PGLN packing increased at the oil-water interface, higher salt concentrations may screen the electrical repulsion between droplets enough to allow coalescence.…”
Section: Emulsion Production and Efficiencymentioning
confidence: 89%
“…At 1 mg/mL concentrations for both grafting densities, however, LPAM100 might instead exhibit smaller droplet sizes because there are more particles in solution compared to the emulsions containing higher molecular-weight LPAM700, as an inverse correlation between particle concentration and droplet size for Pickering emulsions has been established [46]. Additionally, some emulsions have shown increasing droplet size with increasing dispersed phase volume fraction [8,45,49], although explanations for this effect vary. For PGLN systems, it may well be that as the cyclohexane volume fraction increased, there were not enough PGLNs in solution to stabilize an increase in interfacial area associated with more cyclohexane.…”
Section: Emulsion Production and Efficiencymentioning
confidence: 99%
“…Therefore, the system tended to be unstable due to the limited amount of surfactants [51]. Accordingly, increasing the water percentage in the emulsion could reduce the stability of the produced nanoemulsion (55). Also, with the increase in water loading, there occurs an increase in the size of water droplets; this may be attributed to the constant energy dissipated in each case with the increase of water loading, which affect the coarsening value of resultant water droplets to higher water droplet size.…”
Section: Effect Of Water Content and Oil Weight Fractionmentioning
confidence: 99%
“…Also, with the increase in water loading, there occurs an increase in the size of water droplets; this may be attributed to the constant energy dissipated in each case with the increase of water loading, which affect the coarsening value of resultant water droplets to higher water droplet size. The influence of the water-to-oil ratio on droplet size is known to depend quite a lot on the formulation, surfactant nature, the oil characteristic parameter, e.g., its alkane carbon number (ACN) or equivalent (EACN), the water phase salinity, the alcohol type and concentration when applicable, as well as temperature, and sometimes even pressure (55), therefore, the influence of oil weight fraction (WOR) on the stability of w/o nanoemulsions was studied. Oil weight fraction (R) is defined as the weight fraction of oil in the total mixture of oil and water.…”
Section: Effect Of Water Content and Oil Weight Fractionmentioning
confidence: 99%